INNOVATION IN DIGITAL PICTURE CARD-BASED ASSESSMENT IN ARABIC VOCABULARY MASTERY AMONG MADRASAH TSANAWIYAH STUDENTS - Arif Mahfudhi; Zamakhsari Zamakhsari; Anjun Nikmah Wakhidatul Mu’arifah (LP2M IAI Al-Khairat Pamekasan, 2026)
This research investigates an unique evaluation technique that uses digital picture cards to improve Arabic vocabulary competence among seventh-grade pupils in a Madrasah Tsanawiyah. While visual materials have long assisted vocabulary acquisition, their use as a structured assessment tool is still in its early stages, particularly in schools that limit students' access to mobile devices. This gap emphasizes the importance of researching how digital visual evaluations can help with vocabulary development in technology-constrained contexts. The goal of the research is to assess the efficiency of this novel evaluation as well as the difficulties that arise from restricted device access. A qualitative descriptive methodology was used, which included classroom observations, semi-structured interviews with an Arabic instructor and pupils, and documentation of evaluation results. According to findings, the innovation successfully improves students' identification, pronunciation, and understanding of vocabulary by forming strong visual links, while also boosting confidence and engagement during evaluation. The instructor noticed significant gains in accuracy and memory throughout assessment cycles. However, limitations arose since students could not use personal devices, forcing reliance on projectors and computer labs, which limited individual engagement with digital media. Despite these limitations, the novel assessment methodology is still effective and well received. The research suggests improving technology infrastructure and implementing more favorable policies to promote the long-term usage of digital breakthroughs in Arabic learning assessment.